Improving Reading Comprehension By Using Internet Of The Fourth Semester Students Of Stiba Persada Bunda - gunaldi masbiran (Indonesian Journal of Integrated English Language Teaching, 2020)
The goal of this research was to get information whether the students’ reading comprehension could be improved through Internet using at the Fourth Semester Students of School of  Foreign Language at Persada Bunda. The cases were some students’ reading comprehension still low or below standard passing of test. The research was classroom action research. The participants of this research were the Fourth Semester Students of School of  Foreign Language at Persada Bunda. They are consisted of 12 students. This research was held into two cycles, each cycle consisted of three meetings. The research data were divided into two major types namely, quantitative and qualitative data. The quantitative data were taken through reading comprehension test. The qualitative data were collected through observation, and field notes. The result of the analysis showed that the students grades improved after internet using. The improvement happened on each cycle at the research. The improvement of students’ reading comprehension scores were influenced by factors such as motivation, interest, and classroom atmosphere. Thus, it was concluded that internet using can improve students’ reading comprehension. The internet using  also increases students’ speed in reading comprehension that can be used by students of School of Foreign Language at Persada Bunda. Therefore, the internet using is recommended to be used by the students and lecturer in teaching and learning reading comprehension at the School of Foreign Language of Persada Bunda.